Os Centros de Reabilitação de Animais Silvestres (CRAS) no estado de São Paulo e os impactos da pandemia da COVID-19 sobre essas instituições - Aroli, Isabela Roman [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The illegal animal trade is one of the main threats to biodiversity, as well as a probable cause of the emergence of several diseases, such as COVID-19. Wildlife trafficking is considered the third most lucrative criminal activity in the country, second only to the arms and drug trade. When animals that are victims of this crime are confiscated by government authorities, they are responsible for their proper disposal. The most commonly chosen solution is the reintroduction of these animals into nature, an activity that is performed by the Wild Animal Rehabilitation Centers in their release areas. With the advent of the proliferation of the new coronavirus (SARS-CoV-2), the human and economic losses are undeniable, but little is known about the consequences of the pandemic on the conservation of fauna and flora. Given the importance of understanding this aspect of the pandemic and the difficulty of finding centralized information about Wild Animal Rehabilitation Centers in the state of São Paulo, I carried out this work with the following objectives and results: production of a systematic review on the history of Wild Animal Rehabilitation Centers in Brazil, highlighting the its functions and importance for the conservation of fauna; outlining the profiles of Wild Animal Rehabilitation Centers present in the state of São Paulo and analysis of the consequences of the COVID-19 pandemic on the functioning of these institutions. To characterize the Wild Animal Rehabilitation Centers in São Paulo, research was carried out on platforms such as Google Scholar and Scielo and I got in touch with the Wild Animal Rehabilitation Centers through a questionnaire sent by email, in which questions about its functioning, structure, location and animals were addressed. who receive. Of the 18 institutions contacted, we obtained responses from only four Wild Animal Rehabilitation Centers, which confirmed the inaccessibility of data from these institutions. However, based on a general analysis of the responses received, it was observed that the pandemic scenario had negative consequences for these organizations, whether due to the loss of employees, investments or the drop in the release of animals. Unfortunately, as observed in this research, access to data from these organizations is restricted, which makes it difficult to carry out works like the one presented. With greater transparency and accessibility to information, it would be possible to create joint initiatives between the Centers and to carry out scientific research to improve conservation actions.

O comércio ilegal de animais é uma das principais ameaças à biodiversidade, assim como provável causa do surgimento de diversas doenças, como a COVID-19. O tráfico de vida silvestre é considerada a terceira atividade criminosa mais lucrativa no país, perdendo apenas para o comércio de armas e drogas. Quando os animais vítimas desse crime são confiscados por autoridades governamentais, estas são responsáveis pela sua destinação de forma adequada. A solução mais comumente escolhida é a reintrodução desses animais na natureza, atividade que é executada pelos Centros de Reabilitação de Animais Silvestres (CRAS) em suas áreas de soltura. Com o advento da proliferação do novo coronavírus (SARS-CoV-2), as perdas humanas e econômicas são inegáveis, porém pouco se sabe ainda sobre as consequências da pandemia na conservação da fauna e flora. Visto a importância de entender esse aspecto da pandemia e a dificuldade de encontrar informações centralizadas sobre os CRAS no estado de São Paulo, realizei esse trabalho com os seguintes objetivos e resultados: produção de uma revisão sistemática sobre o histórico dos CRAS no Brasil, ressaltando as suas funções e importância para a conservação de fauna; delineamento dos perfis dos CRAS presentes no estado de São Paulo e análise das consequências da pandemia da COVID-19 sob o funcionamento dessas instituições. Para caracterizar os CRAS em São Paulo foram feitas pesquisas em plataformas como o Google Scholar e Scielo e entrei em contato com os CRAS a partir de um questionário enviado por e-mail, em que foram abordadas questões sobre seu funcionamento, estrutura, localização e animais que recebem. De 18 instituições contactadas, obtivemos respostas de apenas quatro CRAS, o que confirmou a inacessibilidade aos dados dessas instituições. Porém, a partir de uma análise geral das respostas recebidas, observou-se que o cenário pandêmico trouxe consequências negativas para essas organizações, seja por perda de funcionários, investimentos ou pela queda na soltura de animais. Infelizmente, como observado nesta pesquisa, o acesso aos dados dessas organizações é restrito, o que dificulta a realização de trabalhos como este apresentado. Com maior transparência e acessibilidade às informações, seria possível criar iniciativas conjuntas entre os Centros e a realização de pesquisas científicas para melhoria das ações conservacionistas.
The wild animal rehabilitation centers in the state of São Paulo and the impacts of the COVID-19 pandemic on these institutions
Keywords: Nature conservation; Questionnnaries; Biodiversity conservation; Conservação da natureza; Questionários; Biodiversidade conservação